Structural design, degradation and condition assessment of cycle paths - Larsson, Martin ; 0000-0002-0334-9940 (2025)
A shift in modal share from car driving to cycling has many benefits, e.g., health benefits from increased physical activity and less pollution and congestion. A smooth cycle path surface with sufficient friction is important for cyclist traffic safety, comfort and level of service. Cracks and surface unevenness are frequent maintenance-related deficiencies associated with the degradation of the structure. A purpose of this thesis is to identify degradation factors specific for cycle paths, through a state-ofthe- art literature review. The review is complemented by four appended papers. Paper A analyses the stated distress modes and causes reported on Swedish municipal cycle paths with respect to climatic and population data. Paper B evaluates a novel method for condition assessments on cycle paths related to cycling comfort—the Bicycle Measurement Trailer. Paper C proposes alternative deflection bowl parameters for structural evaluation of cycle paths from in-situ falling weight deflectometer and light weight deflectometer measurements. Paper D reports on the results of full-scale testing on instrumented cycle path structures. The main results from the papers indicate that surface roughness and unevenness, longitudinal cracks and edge deformations are the most common distress modes. The main reasons behind this distress are structural interventions, tree roots, frost heave and heavy vehicles. The load-bearing capacity close to the pavement edge and at increased moisture content is reduced. The proposed alternative approaches for cycle path condition assessment were able to assess the surface roughness and evenness, along with the structural condition, for practical applications on the investigated cycle paths. The conclusions of the thesis suggest that the structural design principles for cycle paths in the Swedish structural design manual needs to be updated. Models that better describe the behaviour of thin-surfaced asphalt pavements, especially with respect to climate, should be developed. More studies are recommended to validate the proposed condition assessment approaches.
Keywords: cykelvägar; nedbrytning; vägskador; strukturell dimensionering; tillståndsbedömningar; tunna asfaltkonstruktioner; cycle paths; degradation; distress; structural design; condition assessment; thin surfaced asphalt pavements